Selected physics measurements for the LHCB experiment and the radiation monitoring system - V. M. Iakovenko; O. Yu. Okhrimenko; V. M. Pugatch; S. Barsuk; M.-H. Schune (Ядерна фізика та енергетика)
The LHCb experiment at the Large Hadron Collider (LHC) is dedicated to studies of rare phenomena in -and decays in order to precisely constrain the Standard Model parameters and search for beyond Standard Model signatures. The LHCb detector is fully installed and commissioned; first data from pp collisions are being experienced. Physics performance of the LHCb experiment in constraining Standard Model parameters is illustrated with the expected reach on the CKM angle measurements, mixing phases and the angle of unitarity triangle. New physics search in the b-sector is discussed at the examples of rare decays and , as well as photon helicity studies in the mode. Radiation level measurement for the silicon inner tracker operation and beam condition monitoring with the Radiation Monitoring System, developed at Kiev Institute for Nuclear Research, are discussed.